Social Labs: A Cooperative Participatory Methodology for Fieldwork - Daher, Liana; Gianni, Robert (Italian Sociological Review, 2025)
Social Labs is a methodology that belongs to the broad context of participatory approaches but seeks to distinguish itself through a practical vocation, aimed at promoting concrete actions in contextual settings. Social Labs can be understood as dynamic platforms where societal actors collaboratively experiment with ad-hoc strategies to foster social inclusion and address radicalisation and polarisation. The process involves three iterative activities: critical policy discussions, social experiment design and implementation, and outcome reflection for continuous learning. Social labs share with other participatory processes such as focus groups and multistakeholder workshops. What is unique about this methodological approach is that it is not expert oriented, but cooperative. It is also characterised by a strong action-oriented approach, and therefore does not necessarily require a thorough expertise, but it rather builds on common experiences and the desire to be involved in change-making. In this sense, it appears promising for addressing the shortcomings of traditional research methodologies, which tend to focus on theoretical aspects, or on policies that are not sufficiently effective in countering social phenomena of a more complex form. However, the experimental nature of this methodology, which is also its strength, requires a continuous process of validation and correction on the basis of the results obtained in specific areas. Accordingly, the special issue will identify the salient aspects of this methodology, offer an overview of some case studies and integrate the two aspects in order to strengthen active participation practices as a method for addressing major social challenges.